Az Intézményes forradalmi párt (PRI) térvesztése – az 1988-as, 1994-es, 2000-es és 2006-os választások tükrében - Szente-Varga, Mónika (Acta Scientiarum Socialium, 2012)
Based primarily on election campaigns, public opinion surveys (Consulta Mitofsky, Latinobarometro) and the official election results, this study analyses how and to what extent the Institutional Revolutionary Party, that governed Mexico for more than 70 years, has lost power. To what extent can the elections of 2000, that changed the political system, be considered as a break with the past or part of an on-going process? Why did the PRI achieve the worst election results in its history in 2006? What new political dividing lines were formed in Mexico after the disappearance of the hegemony of the PRI? What can we expect at the 2012 presidential elections?